2022
DOI: 10.3389/ti.2022.10182
|View full text |Cite
|
Sign up to set email alerts
|

Differential IgG4-Producing Plasma Cell Infiltration in Non- and Post-Transplant Plasma Cell Hepatitis

Abstract: Autoimmune hepatitis (AIH), post-transplant recurrent AIH (rAIH), and plasma cell-rich rejection (PCR) are clinical diagnoses with the shared histopathologic hallmark of plasma cell hepatitis (PCH). As these histologically and serologically indistinguishable diagnoses are differentiated by clinical context, it remains uncertain whether they represent distinct immunologic phenomena. Improved understanding of immunoglobulin subclass 4-producing plasma cells (IgG4-PC) has brought attention to IgG4 as an immunophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Additionally, their work also suggests that serologic evaluation of anti-GSTT1 antibodies may be a useful marker in PCR diagnosis and disease response to corticosteroid therapy (1). It is satisfying that the findings from our histopathologic assessment of post-transplant plasma cell hepatitis correlates with their observations (2).…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Additionally, their work also suggests that serologic evaluation of anti-GSTT1 antibodies may be a useful marker in PCR diagnosis and disease response to corticosteroid therapy (1). It is satisfying that the findings from our histopathologic assessment of post-transplant plasma cell hepatitis correlates with their observations (2).…”
mentioning
confidence: 55%
“…A study in which IgG4 Positivity and anti-GSTT1 antibodies are identified in the same subjects is warranted. Additionally, as our works only evaluated a combined 28 cases of PCR and rAIH, further studies with a larger cohort are needed (1,2).…”
mentioning
confidence: 99%